PARTICLE SWARM OPTIMIZATION FOR INVERSE KINEMATICS SOLUTION AND TRAJECTORY PLANNING OF 7-DOF AND 8-DOF ROBOT MANIPULATORS BASED ON UNIT QUATERNION REPRESENTATION - Abdor-Sierra, Javier Alexis; Merchán-Cruz, Emmanuel Alejandro; Sánchez-Garfias, Flavio Arturo; Rodríguez-Cañizo, Ricardo Gustavo; Portilla-Flores, Edgar Alfredo; Vázquez-Castillo, Valentín (Journal of Applied Engineering Science, 2021)
Finding the inverse kinematic solution of a serial manipulator has always attracted the attention of optimization enthusiasts, as the solution space is highly nonlinear and, depending on the number of degrees of freedom, has multiple solutions. In the literature, one can find several proposed solutions using heuristic techniques; however, for highly redundant manipulators, e.g., seven or more, the discussions focused on minimizing the positional error. In this paper, a metaheuristic approach is presented to solve not only the inverse kinematics of a 7 and 8 DOF manipulators but the proposed algorithm is used to find the robot’s poses for trajectory planning where the robot is required to meet the desired position and orientation based on quaternion representation of each point along the path. The metaheuristic approach used in this paper is particle swarm optimization (PSO), where the unit quaternion is used in the objective function to find the orientation error. The results prove that the use of the unit quaternion representation improved the performance of the algorithm and that our approach can be used not only for individual poses but for trajectory planning.